Growth regulators in increasing pedicel thickness and shelf-life in ’Tas-A-Ganesh’ grapes (Vitis vinifera) grafted on ’1613 C’ rootstock - RAMTEKE, S D; SOMKUWAR, R G; SHIKHAMANY, S D; SATISHA, J (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 1997-99 to study the effect of growth regulators to increase pedicel thickness and shelf-life in ’Tas-A-Ganesh’ grapes (Vitis vinifera L.) grafted on ’1613 C’ rootstock. Treatments With growth regulators like 4-CPA, 6-BA and CPPU increased the pedicel thickness by 19.4% and enhanced the shelf-life (PLW) by 2 days compared with the 2 applications of GA3 alone. Berry drop and berry rot were reduced to 32.25% and 35.96%, respectively, with the delay in pedicel browning by 32.5% at day 5 in shelf after removal of samples from the cold storage at day 30. Among the growth regulators, CPPU along with GA3 was more effective in increasing the shelf-life when the clusters were applied twice in 2 ppm aqueous solution, once at 6 mm berry Size stage and again at veraison stage With 25 ppm GA3 at 3 mm berry size and 6 mm berry size stage. Among the different treatments, dipping bunches first with GA3 @ 25 ppm at 3 mm berry size, followed by combination of GA3 @ 25 ppm and CPPU @ 2 ppm at 6 mm berry Size and final dipping of bunches with CPPU @ 2 ppm during veraison was found effective compared with other treatments like GA in combination either with 4-CP A or 6 BA.